Coating solution containing cellulose nanocrystals
Patent Information
- Application Number
- JP2021002902
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-16
- Filing Date
- 2021-01-12
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-01-12
AI Technical Summary
【0010】 本発明のセルロースナノクリスタル含有コーティング液においては、セルロースナノクリスタルとしてガスバリア性及び取扱い性に優れた分散液を使用することにより、生産性及び経済性良く、ガスバリア性に優れた塗膜を形成可能なコーティング液を調製することができる。 本発明で使用するセルロースナノクリスタル含有コーティング液では、セルロースナノクリスタル分散液のレーザ回折式粒度分布測定装置によるセルロースナノクリスタルの平均粒径が12.2μm以下且つメディアン径が12.6μm以下且つモード径が17.0μm以下であり、繊維長が短いセルロースナノクリスタルが凝集することなく、均一に分散している。これにより塗工時のハンドリング性に優れ、塗工表面の平滑性にも優れている。また、得られる塗膜はガスバリア性にも優れている。 また本発明のセルロースナノクリスタル含有コーティング液においては、セルロースナノクリスタルの水酸基と多価カルボン酸が緻密な架橋膜を構成することによる優れたガスバリア性と、水溶性高分子及び無機層状化合物が含有されていることに基づくガスバリア性の向上とが相俟って、高湿度条件下においても優れたガスバリア性を発現することが可能になる。 更にまた、本発明の多価カチオン樹脂及びセルロースナノクリスタルを含有する層が形成されて成る成形体においては、セルロースナノクリスタル間の緻密な自己組織化構造を維持しながら、セルロースナノクリスタル間に多価カチオン樹脂が自然拡散して介在した混合状態になっており、ナノセルロースの自己組織化構造が多価カチオンによって更に強化されていることから、ナノセルロースだけで発現されるガスバリア性よりも優れたガスバリア性を有する。
Smart Images

Figure 0007631812000005 
Figure 0007631812000001 
Figure 0007631812000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a cellulose nanocrystal-containing coating liquid, and more specifically to a cellulose nanocrystal-containing coating liquid that is easy to handle during application and can exhibit excellent gas barrier properties. [Background technology]
[0002] Nanocellulose has been proposed for use in a variety of applications as an advanced biomass raw material, functional additive, film composite material, etc. In particular, materials such as membranes made of cellulose nanofibers (CNF) and laminates containing cellulose nanofibers are known to have excellent gas barrier properties, such as oxygen barrier properties, because they suppress the dissolution and diffusion of gases due to the strong hydrogen bonds and cross-linking interactions between the cellulose fibers, and barrier materials using cellulose nanofibers have been proposed. In order to reduce the size of cellulose fibers, in addition to mechanical treatment, chemical treatment is carried out to introduce hydrophilic functional groups, such as carboxyl groups or phosphate groups, into the hydroxyl groups of cellulose. This not only reduces the energy required for the reduction process, but also improves the barrier properties and dispersibility in aqueous solvents.
[0003] Dispersions using such cellulose nanofibers are also known. For example, Patent Document 1 listed below proposes a dispersion in which cellulose nanofibers having a crystallinity of 70% or more, a degree of polymerization of 160 or less as measured by a viscosimetry using a copper ethylenediamine solution, and a fiber diameter of 50 nm or less are dispersed in a dispersion medium. Furthermore, Patent Document 2 listed below proposes a dispersion in which cellulose nanofibers having a number average fiber length of 250 nm or less and a number average fiber diameter of 2 to 5 nm are dispersed in a dispersion medium. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-256546 A [Patent Document 2] International Publication 2014 / 061485 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the cellulose nanofiber dispersion described in Patent Document 1, the process for preparing the cellulose nanofibers to be dispersed in the dispersion medium requires a process for reducing the viscosity of the cellulose nanofibers that have been chemically treated with a TEMPO catalyst, or a process for atomizing the cellulose nanofibers into nanofibers, and this is not fully satisfactory in terms of productivity or economic efficiency. Furthermore, since the cellulose nanofibers have a long fiber length, they are not satisfactory in terms of gas barrier properties, and although it is possible to obtain high gas barrier properties by shortening the fiber length, further processing is required for this, which is less economical. Furthermore, in the above-mentioned Patent Document 2, short fiber length cellulose nanofibers are prepared that can reduce the viscosity of the dispersion liquid in order to improve the dispersibility of the dispersion liquid. However, special raw materials must be used to prepare short fiber length cellulose nanofibers, which is also inferior in productivity and cost-effectiveness.
[0006] Cellulose nanocrystals (CNCs), which are made by hydrolyzing cellulose fibers with strong acids, are known as nanocelluloses with shorter fiber lengths than cellulose nanofibers. Because cellulose nanocrystals have short fiber lengths, they are easy to handle when applied and have excellent smoothness on the coated surface. However, cellulose nanocrystals generally have inferior gas barrier properties compared to cellulose nanofibers with carboxyl groups introduced as described above. The inventors have discovered that cellulose nanocrystals can exhibit excellent gas barrier properties by containing a large number of anionic functional groups (Patent Application No. 2018-177610). However, such cellulose nanocrystals are generally solidified into a powder form from the viewpoints of storage and transportability, etc., and in order to obtain a dispersion, it is necessary to disperse the powdered cellulose nanocrystals in a dispersion medium while suppressing aggregation, which is also unsatisfactory in terms of productivity and economy. Furthermore, the present inventors' research has revealed that a dispersion in which such solidified (powdered) cellulose nanocrystals are dispersed reduces the gas barrier properties of cellulose nanocrystals containing anionic functional groups.
[0007] Therefore, an object of the present invention is to provide a cellulose nanocrystal-containing coating liquid that uses a cellulose nanocrystal dispersion liquid that has excellent gas barrier properties and ease of handling, and that is capable of efficiently forming a crosslinked structure in which cellulose nanocrystals are uniformly dispersed. Another object of the present invention is to provide a molded article having a cellulose nanocrystal-containing layer that has excellent gas barrier properties and interlayer adhesion. [Means for solving the problem]
[0008] According to the present invention, there is provided a cellulose nanocrystal-containing coating liquid which contains a cellulose nanocrystal dispersion, a water-soluble polymer, an inorganic layered compound and a polycarboxylic acid, characterized in that the cellulose nanocrystals in the cellulose nanocrystal dispersion have an average particle size of 12.2 μm or less, a median diameter of 12.6 μm or less and a mode diameter of 17.0 μm or less, as measured with a laser diffraction particle size distribution measuring device. In the cellulose nanocrystal-containing coating liquid of the present invention, 1. The water-soluble polymer is polyvinyl alcohol, and is contained in an amount of 0.1 to 50 parts by mass per 100 parts by mass of cellulose nanocrystals (solid content); 2. The inorganic layered compound is mica, and is contained in an amount of 0.1 to 50 parts by mass per 100 parts by mass of cellulose nanocrystals (solid content); 3. The polycarboxylic acid is citric acid, and is contained in an amount of 0.1 to 50 parts by mass per 100 parts by mass of cellulose nanocrystals (solid content); 4. The cellulose nanocrystal dispersion has a solid content of cellulose nanocrystals of 2% by mass and a visible light transmittance of 2.1%T or more at 600 nm when dispersed in water; is preferred.
[0009] According to the present invention, there is also provided a molded article comprising a layer containing a polyvalent cationic resin and cellulose nanocrystals formed on a substrate, the layer containing the cellulose nanocrystals (solid content) being 1.0 g / m 2 When the amount is 3.8cc / m2, the oxygen permeability (23℃ 50%RH) is 3.8cc / m2 2 The molded article is characterized in that its viscosity is less than 1000 psi.day·atm. In the molded article of the present invention, it is preferable that the polyvalent cationic resin is polyethyleneimine. Effect of the Invention
[0010] In the cellulose nanocrystal-containing coating liquid of the present invention, by using a dispersion liquid having excellent gas barrier properties and ease of handling as cellulose nanocrystals, it is possible to prepare a coating liquid capable of forming a coating film having excellent gas barrier properties with good productivity and economic efficiency. In the cellulose nanocrystal-containing coating liquid used in the present invention, the average particle size of the cellulose nanocrystals measured by a laser diffraction particle size distribution analyzer is 12.2 μm or less, the median diameter is 12.6 μm or less, and the mode diameter is 17.0 μm or less, and the cellulose nanocrystals having short fiber lengths are uniformly dispersed without aggregation. This provides excellent handling during coating and excellent smoothness of the coating surface. The resulting coating film also has excellent gas barrier properties. Furthermore, in the cellulose nanocrystal-containing coating liquid of the present invention, the excellent gas barrier properties due to the hydroxyl groups of the cellulose nanocrystals and the polycarboxylic acid forming a dense crosslinked film, combined with the improved gas barrier properties due to the inclusion of a water-soluble polymer and an inorganic layered compound, make it possible to exhibit excellent gas barrier properties even under high humidity conditions. Furthermore, in a molded article formed by forming a layer containing the polyvalent cationic resin of the present invention and cellulose nanocrystals, the polyvalent cationic resin naturally diffuses between the cellulose nanocrystals while maintaining the dense self-organized structure between the cellulose nanocrystals, creating a mixed state in which the polyvalent cationic resin is naturally diffused and interposed between the cellulose nanocrystals. Since the self-organized structure of the nanocellulose is further strengthened by the polyvalent cations, the article has gas barrier properties that are superior to those exhibited by nanocellulose alone. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a diagram showing a method for calculating an arbitrary percentage of particle size in particle size distribution data. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] (Cellulose nanocrystal-containing coating solution) In the cellulose nanocrystal-containing coating liquid of the present invention, by containing a water-soluble polymer and an inorganic layered compound together with the cellulose nanocrystal dispersion, it is possible to exhibit excellent gas barrier properties even under high humidity conditions. That is, the hydroxyl group-containing polymer can form a dense crosslinked structure together with the cellulose nanocrystals, and the gas barrier properties of the resulting coating film are significantly improved. In addition, since the layered inorganic compound has swelling and cleavage properties, the cellulose nanocrystals penetrate into the inorganic layered compound so as to widen the gap between the layers, and are combined, and the bypass effect of the permeating gas obtained by the layered inorganic compound and the crosslinked structure by the cellulose nanocrystals combine to make it possible to exhibit excellent gas barrier properties even under high humidity conditions.
[0013] The coating liquid of the present invention is also characterized in that the cellulose nanocrystals in the cellulose nanocrystal dispersion have an average particle size of 12.2 μm or less, a median diameter of 12.6 μm or less, and a mode diameter of 17.0 μm or less, as measured with a laser diffraction particle size distribution analyzer. This indicates that the cellulose nanocrystals in the coating liquid of the present invention are in a state in which the cellulose nanocrystals, which have short fiber lengths, are uniformly dispersed without agglomeration. Particle size distribution is an index that indicates the size (particle diameter) of particles contained in the sample particle group of the dispersion liquid to be measured, and the ratio (relative particle amount with the whole being 100%). Particle sizes are identified from the light intensity distribution data pattern in the laser diffraction / scattering method using a laser diffraction particle size distribution device, and the volume-based particle size distribution is calculated. It is also possible to calculate the number-based particle size distribution based on the volume-based particle size distribution. When a laser diffraction particle size analyzer irradiates a particle group to be measured with a laser beam, a spatial light intensity distribution pattern of diffracted and scattered light is generated, of which the light intensity distribution pattern of the forward scattered light is focused by a lens to form a ring-shaped diffracted and scattered image on the detection surface located at the focal distance. This is detected by a ring sensor with detection elements arranged concentrically. Side scattered light and backward scattered light are detected by a side scattered light sensor and backward scattered light sensor, respectively. In this way, the light intensity distribution pattern is detected using various detection elements to obtain light intensity distribution data. When cellulose nanocrystals are present in a low concentration in the dispersion, the average particle size, median diameter, and mode diameter of the cellulose nanocrystals can be determined by analyzing the measurement results of a laser diffraction particle size analyzer. A dispersion in which the average particle size, median diameter, and mode diameter of the cellulose nanocrystals in the dispersion are within the above ranges has good fiber dispersion, excellent gas barrier properties and handling properties during coating, as well as the advantage of excellent smoothness of the coating surface.
[0014] Particle size distribution is usually expressed as the particle amount (accumulation or frequency) relative to the particle size scale. In addition, in the laser diffraction and scattering method, which is the measurement principle of laser diffraction particle size distribution measurement devices, particle size distribution is obtained based on the light intensity distribution pattern of diffracted and scattered light calculated on the assumption that particles are spherical. Therefore, particle size distribution measurement is always performed based on the premise or assumption that particles are spherical. In the case of fibrous particles such as cellulose nanocrystals, the particle size distribution is relatively broad, with the short diameter of the fibrous particles roughly corresponding to the lower limit of the distribution and the long diameter to the upper limit of the distribution. This is because the orientation of the fibrous particles inside the cell is considered to be random, and even if the orientation of the particles is somewhat uniform, the shape of the sensor that detects the diffracted and scattered light is 1 / 4 of a circle, so that the diffracted and scattered light from only a certain direction is not detected. When fibrous particles of various shapes and sizes are included, the distribution range of the measurement results will spread from the smallest short diameter to the largest long diameter. Even in the case of fibrous particles, if the variation in the shape and size of the particles included in the particle group being measured increases, the distribution range will widen, and if the variation decreases, the distribution range will narrow. If the shape and size increase, the particle size distribution will shift to the larger side overall, and if the shape and size decrease, the particle size distribution will shift to the smaller side overall. If the fibrous particles are aggregated, the particle size distribution will shift to the larger side overall, and if they are dispersed, the particle size distribution will shift to the smaller side overall. In this way, the fibrous properties of cellulose nanocrystals can be quantitatively evaluated using a laser diffraction particle size analyzer.
[0015] The average particle size is calculated based on a logarithmic scale by multiplying each particle size value by the relative particle amount (difference %) and dividing by the total relative particle amount (100%). Specifically, first the particle size range to be measured (maximum particle size: x1, minimum particle size: xn+1) is divided into n, and each particle size interval is defined as [xj, xj+1] (j=1, 2,...n). In this case, the division is equal on a logarithmic scale. Furthermore, the representative particle size in each particle size interval is calculated using the following formula (1) based on the logarithmic scale. Even though it is called the representative particle size, since the logarithm is taken, it is no longer a unit of particle size at this point.
[0016]
number
[0017] Furthermore, if qj (j = 1, 2, . . . n) is the relative particle amount (difference %) corresponding to the particle size interval [xj, xj+1] and the total for all intervals is 100%, the average value μ on the logarithmic scale can be calculated using the following formula (2).
[0018]
number
[0019] This μ is a value on a logarithmic scale and does not have a unit of particle size, so it is converted to 10 μ In other words, we are calculating 10 to the power of μ. μ is the average particle size.
[0020] Particle size distribution data is expressed as cumulative % or frequency % on a particle size scale, but can also be expressed as particle size on a cumulative % scale. For example, the particle size at the point where the cumulative % distribution curve crosses the 10% horizontal axis can be called the 10% diameter, the particle size at the point where it crosses the 50% horizontal axis can be called the 50% diameter, and the particle size at the point where it crosses the 90% horizontal axis can be called the 90% diameter, and any cumulative % can be used as necessary. The calculation method for any % particle size is shown in Figure 1 and formulas (3) and (4).
[0021]
number
[0022] Accumulated %Q a Any % particle size x a Find this x a The two particle sizes on either side of x j+1 and x j Accumulated %Q in j+1 and Q j When is known, the cumulative %Q a Any % particle size x a can be calculated using the above formulas (3) and (4). The 50% particle size is the median size, and Q a The median diameter can be calculated by assuming that the ratio of the frequency of occurrence (%) is 50%. The mode diameter can be calculated by the particle size with the highest frequency of occurrence (%).
[0023] The upper limits of the average particle size, median diameter, and mode diameter of the cellulose nanocrystals in the cellulose nanocrystal dispersion used in the present invention measured by a laser diffraction particle size distribution analyzer are as described above, but as these values become smaller, the transparency and gas barrier properties, or the handling properties during coating and the smoothness of the coating surface are improved, so it is desirable that these values are as small as possible, and therefore the lower limits of these values are not particularly limited. In addition, as long as the upper limits of these values are not more than the above-mentioned values, they can be appropriately set according to the required transparency and gas barrier properties, and are not particularly limited, but the average particle size is preferably 12.2 μm or less, particularly 4.0 μm or less, the median diameter is preferably 12.6 μm or less, particularly 5.0 μm or less, and the mode diameter is preferably 17.0 μm or less, particularly 5.0 μm or less.
[0024] [Cellulose nanocrystal dispersion] The cellulose nanocrystal dispersion contained in the coating liquid of the present invention may be any dispersion in which the dispersoid is cellulose nanocrystals obtained by acid hydrolysis of cellulose raw material with hydrochloric acid, sulfuric acid, etc., and the dispersion medium is water, etc., but it is preferable that the cellulose nanocrystal dispersion is a cellulose nanocrystal dispersion having a visible light transmittance at 600 nm of 2.1%T or more when the solid content of the cellulose nanocrystals is 2 mass%. As described later, it is important that such a dispersion is not a cellulose nanocrystal dispersion that has not been solidified (never-dried) during preparation of the dispersion, i.e., a dispersion that has been solidified into a powder form or the like by spray drying or the like and then redispersed. That is, cellulose nanocrystals that have been solidified by drying are unlikely to have the fibers oriented in the dispersion, making it difficult to form a dense self-organized structure, and have inferior gas barrier properties compared to dispersions that have not been solidified. This is also clear from the results of the examples described later, and in the coating liquid of Comparative Example 1, which has the same composition as Examples 1 and 2 except for using a dispersion obtained by redispersing solidified cellulose nanocrystals, the average particle size, median size, and mode size of the cellulose nanocrystals measured by dynamic light scattering measurement are outside the ranges specified in the present invention, and the visible light transmittance at 600 nm when the solid content of the cellulose nanocrystals is 2% by weight is 2.0%T, which is inferior in transparency and gas barrier properties.
[0025] In addition, in the cellulose nanocrystal dispersion liquid contained in the coating liquid of the present invention, all cellulose nanocrystals including those hydrolyzed by hydrochloric acid treatment can be used as the cellulose nanocrystal, but cellulose nanocrystals hydrolyzed by sulfuric acid treatment are preferred. That is, cellulose nanocrystals include those obtained by acid hydrolysis of cellulose fibers by sulfuric acid treatment or hydrochloric acid treatment, but cellulose nanocrystals obtained by sulfuric acid treatment are advantageously used because they already have sulfate groups and / or sulfo groups that can contribute to the formation of a self-organized structure. It is particularly preferable that the cellulose nanocrystal contains anionic functional groups such as sulfate groups and / or sulfo groups and carboxyl groups in a total amount of more than 0.01 mmol / g and not more than 4.0 mmol / g. By having the total amount of anionic functional groups in the above range, it is possible to form a sufficient self-organized structure while maintaining the crystal structure of the cellulose nanocrystal, and it is possible to express excellent gas barrier properties. In this specification, the sulfate group is a concept that includes sulfate ester groups. Furthermore, cellulose nanocrystals having a fiber diameter of 50 nm or less, particularly in the range of 2 to 50 nm, a fiber length of 100 to 500 nm, an aspect ratio of 5 to 50, and a crystallinity of 60% or more, particularly 70% or more, can be suitably used.
[0026] The anionic functional group possessed by the cellulose nanocrystal of the present invention is determined by the method of hydrophilization treatment of the cellulose nanocrystal described later, and is particularly preferably a carboxyl group, a phosphate group, a sulfate group, or a sulfo group, which allows the aforementioned self-organized structure to be formed efficiently and improves the gas barrier property.
[0027] <Hydrophilic Treatment> As described above, the cellulose nanocrystal dispersion contained in the coating liquid of the present invention is preferably prepared by subjecting cellulose nanocrystals having sulfate groups and / or sulfo groups to a hydrophilization treatment to adjust the amount of sulfate groups and / or sulfo groups, or by introducing anionic functional groups such as carboxyl groups and phosphate groups to the hydroxyl group at the 6-position of cellulose, thereby resulting in a cellulose nanocrystal dispersion in which the total amount of anionic functional groups such as sulfate groups, sulfo groups, carboxyl groups, phosphate groups, etc. is more than 0.01 mmol / g and not more than 4.0 mmol / g, particularly in the range of 0.17 to 2.0 mmol / g. As the hydrophilization treatment, a never-dry treatment or a combination of a never-dry treatment and a treatment using any of water-soluble carbodiimide, sulfuric acid, sulfur trioxide-pyridine complex, phosphoric acid-urea, TEMPO catalyst, and oxidizing agent is performed. By the treatment using any of carbodiimide, sulfuric acid, and sulfur trioxide-pyridine complex, the amount of sulfate groups and / or sulfo groups in the cellulose nanocrystals is adjusted, and the nanocellulose is further shortened. In addition, by the treatment using any of phosphoric acid-urea, TEMPO catalyst, and oxidizing agent, anionic functional groups of phosphoric acid groups or carboxyl groups are introduced, and the total amount of anionic functional groups in the cellulose nanocrystals is adjusted to the above range. As for the hydrophilization treatment, any one of the treatments may be carried out so long as the total amount of anionic functional groups falls within the above-mentioned range, but the same treatment may be carried out multiple times, or may be carried out multiple times in combination with other treatments.
[0028] <<Hydrophilic treatment using NeverDry treatment>> Cellulose nanocrystals are solidified into powders or the like by drying treatments such as spray drying, heating, and reduced pressure, but during solidification by drying treatment, some of the anionic functional groups contained in the cellulose nanocrystals are eliminated, reducing the hydrophilicity. In other words, a never-dry treatment that does not solidify into powders or the like for cellulose nanocrystals containing anionic functional groups is an example of a hydrophilization treatment. Examples of anionic functional groups include sulfate groups and / or sulfo groups, phosphate groups, and carboxyl groups.
[0029] <<Hydrophilic treatment using carbodiimide>> In the treatment using carbodiimide, cellulose nanocrystals and carbodiimide are stirred in a solvent such as dimethylformamide, sulfuric acid is added thereto, and the mixture is reacted for 5 to 300 minutes at a temperature of 0 to 80° C. to form a sulfate ester. The carbodiimide and sulfuric acid are preferably used in amounts of 5 to 30 mmol and 5 to 30 mmol per gram (solid content) of cellulose nanocrystals. Next, it is preferable to add an alkaline compound such as sodium hydroxide to convert the sulfo groups introduced into the cellulose nanocrystals from H type to Na type in order to improve the yield. Then, impurities are removed by filtration using a dialysis membrane or the like to prepare sulfate and / or sulfo modified cellulose nanocrystals. Examples of carbodiimides include 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, which is a water-soluble compound having a carbodiimide group (-N=C=N-) in the molecule. Dicyclohexylcarbodiimide, which is soluble in organic solvents, can also be used.
[0030] <<Hydrophilic treatment using sulfuric acid>> The cellulose nanocrystals used in the present invention are obtained by hydrolyzing cellulose fibers with sulfuric acid, and these cellulose nanocrystals are further hydrophilized with sulfuric acid. Sulfuric acid is preferably used at 40 to 60% by mass per 1 g (solid content) of cellulose nanocrystals. The reaction is carried out at a temperature of 40 to 60°C for 5 to 300 minutes, and then the mixture is subjected to a filtration process using a dialysis membrane or the like to remove impurities, thereby preparing sulfate and / or sulfo group-modified cellulose nanocrystals.
[0031] <<Hydrophilic treatment using sulfur trioxide-pyridine complex>> In the treatment using a sulfur trioxide-pyridine complex, cellulose nanocrystals are reacted with the sulfur trioxide-pyridine complex in dimethyl sulfoxide at a temperature of 0 to 60°C for 5 to 240 minutes to introduce a sulfate group and / or a sulfo group into the hydroxyl group at the 6-position of the cellulose glycol unit. The sulfur trioxide-pyridine complex is preferably mixed in an amount of 0.5 to 4 g by mass per 1 g (solid content) of cellulose nanocrystal. After the reaction, it is preferable to add an alkaline compound such as sodium hydroxide to convert the sulfate group and / or sulfonate group introduced into the cellulose nanocrystal from the H form to the Na form in order to improve the yield. Thereafter, dimethylformamide or isopropyl alcohol is added, washed by centrifugation or the like, and then impurities and the like are removed by filtration using a dialysis membrane or the like, and the obtained concentrated solution is dispersed in water to prepare a sulfate group and / or sulfonate group-modified cellulose nanocrystal.
[0032] <<Hydrophilic treatment using phosphoric acid-urea>> The hydrophilic treatment using phosphoric acid-urea can be carried out in the same manner as the conventionally known treatment for introducing a phosphate group using phosphoric acid-urea. Specifically, in the presence of a urea-containing compound, a cellulose nanocrystal and a phosphate group-containing compound are reacted at a temperature of 135 to 180°C for 5 to 120 minutes to introduce a phosphate group into the hydroxyl group of the cellulose glucose unit. Examples of the phosphate group-containing compound include phosphoric acid, lithium salt of phosphoric acid, sodium salt of phosphoric acid, potassium salt of phosphoric acid, ammonium salt of phosphoric acid, etc. Among them, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, etc. can be preferably used alone or in combination. The phosphate group-containing compound is preferably added in an amount of 10 to 100 mmol with respect to 10 g (solid content) of the cellulose nanocrystal. Examples of the urea-containing compound include urea, thiourea, biuret, phenylurea, benzylurea, dimethylurea, etc. Among them, urea can be preferably used. The urea-containing compound is preferably used in an amount of 150 to 200 mmol with respect to 10 g (solid content) of the cellulose nanocrystal.
[0033] <<Hydrophilic treatment using TEMPO catalyst>> The hydrophilization treatment using the TEMPO catalyst (2,2,6,6-tetramethylpiperidine-1-oxyl) can be carried out in the same manner as the conventionally known oxidation method using the TEMPO catalyst. Specifically, a hydrophilization reaction is caused in which the hydroxyl group at the 6-position of the cellulose glucose unit is oxidized to a carboxyl group in an aqueous system at room temperature and pressure using the TEMPO catalyst (2,2,6,6-tetramethylpiperidine-1-oxyl). As the TEMPO catalyst, in addition to the above-mentioned 2,2,6,6-tetramethylpiperidine-1-oxyl, derivatives of TEMPO such as 4-acetamido-TEMPO, 4-carboxy-TEMPO, and 4-phosphonoxy-TEMPO can also be used. The amount of the TEMPO catalyst used is 0.01 to 100 mmol, and preferably 0.01 to 5 mmol, per 1 g of cellulose nanocrystal (solid content).
[0034] During the hydrophilization treatment, it is preferable to use a co-oxidant such as an oxidant, bromide or iodide alone or in combination with the TEMPO catalyst. Examples of the oxidizing agent include known oxidizing agents such as halogen, hypohalous acid, halous acid, perhalogen acid or their salts, halogen oxides, and peroxides, and sodium hypochlorite and sodium hypobromite are particularly suitable. The amount of the oxidizing agent is 0.5 to 500 mmol, preferably 5 to 50 mmol, per gram of cellulose nanocrystal (solid content). After a certain period of time has elapsed since the addition of the oxidizing agent, additional oxidizing agent can be added to perform additional oxidation treatment. As the co-oxidizing agent, an alkali metal bromide such as sodium bromide, or an alkali metal iodide such as sodium iodide can be suitably used. The amount of the co-oxidizing agent is 0.1 to 100 mmol, preferably 0.5 to 5 mmol, per 1 g of cellulose nanocrystal (solid content). The reaction medium for the reaction solution is preferably water or an alcohol solvent.
[0035] The reaction temperature for the hydrophilization treatment is in the range of 1 to 50° C., particularly 10 to 50° C., and may be room temperature. The reaction time is preferably 1 to 360 minutes, particularly 60 to 240 minutes. As the reaction proceeds, carboxyl groups are produced in the cellulose, causing a decrease in the pH of the slurry. However, in order to ensure efficient oxidation reaction, it is desirable to maintain the pH in the range of 9 to 12 using a pH adjuster such as sodium hydroxide.
[0036] <Cleaning and fiber defibration processing> Before or after the hydrophilization treatment, the cellulose nanocrystals are washed with water or centrifuged while adding water to wash away the acid, catalyst, etc. used in the hydrophilization treatment. Then, it is preferable to carry out a defibration treatment, but since the cellulose nanocrystals have a short fiber length, this is not necessarily required. In addition, the defibration process may be performed using an ultra-high pressure homogenizer, mixer, grinder, etc. as a micronizing device, and water or the like as a dispersion medium, thereby preparing a dispersion liquid at the same time as the defibration.
[0037] <Preparation of cellulose nanocrystal dispersion> The hydrophilic cellulose nanocrystals are washed to remove the acid, catalyst, etc. used in the hydrophilic treatment by washing with water or by centrifuging while adding water. Next, it is preferable to carry out a defibration process. However, since cellulose nanocrystals have short fiber length, this does not necessarily have to be carried out. However, by carrying out the defibration process using an ultra-high pressure homogenizer, mixer, grinder, etc. as a micronization device and using water or the like as a dispersion medium, it is possible to prepare a dispersion liquid at the same time as defibration.
[0038] The cellulose nanocrystals that have been subjected to hydrophilization treatment or, if necessary, defibration treatment are subjected to dispersion treatment (never-dry treatment) without being solidified (spray-dried to form a powder). Since they are not solidified, there is no need for redispersion, and they are excellent in productivity and economy. Furthermore, since they are not solidified, it is possible to form the dense self-organized structure described above, and it is possible to exhibit excellent gas barrier properties. For the dispersion treatment, a dispersing machine such as an ultrasonic dispersing machine, a homogenizer, or a mixer can be suitably used, and a stirring method using a stirring rod, stirring stone, or the like may also be used. The dispersion medium of the dispersion liquid may be water alone, or may be a mixed solvent of water and an alcohol such as methanol, ethanol, isopropanol, etc., a ketone such as 2-butanone, acetone, etc., or an aromatic solvent such as toluene, etc. The cellulose nanocrystal dispersion preferably contains cellulose nanocrystals (solid content) in the range of 0.1 to 90% by mass, and when dispersed in water with a solid content of 2% by mass, it has a viscosity of 5.5 to 40 mPa·s (rotational viscometer, temperature 30°C, spindle rotation speed 100 rpm) and a zeta potential in the range of -50 to -55 mV, providing excellent handling and coatability. In addition, when dispersed in water with a solid content of 2% by mass, it has a visible light transmittance of 2.1%T or more at 600 nm, providing excellent transparency.
[0039] [Water-soluble polymer] Examples of the water-soluble polymer contained in the coating liquid of the present invention include polyvinyl alcohol, vinyl acetate alcohol copolymer, ethylene-vinyl alcohol copolymer, polyacrylic acid, polymethacrylic acid, carboxymethyl cellulose, starch, etc., and polyvinyl alcohol is preferably used. The polyvinyl alcohol is preferably a fully saponified type having a degree of polymerization of 100 to 10,000. The hydroxyl group-containing polymer is preferably blended in an amount of 0.1 to 50 parts by mass per 100 parts by mass of the cellulose nanocrystal (solid content).
[0040] [Inorganic layered compounds] The inorganic layered compound may be a natural or synthetic compound, a hydrophilic or hydrophobic compound, or a conventional compound known in the art that swells in a solvent and exhibits cleavage, including, but not limited to, kaolinite, dickite, nacrite, halloysite, antigorite, chrysotile, pyrophyllite, montmorillonite, hectorite, mica, tetracylic mica, sodium taeniolite, muscovite, margarite, talc, vermiculite, phlogopite, xanthophyllite, and chlorite, with synthetic mica (hydrophilic and swellable) being preferred. The inorganic layered compound is preferably blended in an amount of 0.1 to 50 parts by mass per 100 parts by mass of the cellulose nanocrystal (solid content).
[0041] [Reactive crosslinking agent] In the coating liquid of the present invention, a polycarboxylic acid having good reaction efficiency is used as a reactive crosslinking agent. Examples of the polycarboxylic acid include alkyl dicarboxylic acids such as citric acid, oxalic acid, and malonic acid, aromatic dicarboxylic acids such as terephthalic acid and maleic acid, and anhydrides thereof, and citric anhydride is particularly suitable. In the coating liquid of the present invention, since the cellulose nanocrystals contain anionic functional groups, they can be stably dispersed without aggregation even under acidic conditions, and therefore the above-mentioned polyvalent carboxylic acids can be suitably used. The polyvalent carboxylic acid is preferably blended in an amount of 0.1 to 50 parts by mass per 100 parts by mass of the cellulose nanocrystal (solid content).
[0042] [others] In the coating liquid of the present invention, it is preferable to contain an acid catalyst together with the crosslinking agent made of the polyvalent carboxylic acid. Examples of such an acid catalyst include sulfuric acid, acetic acid, and hydrochloric acid, and sulfuric acid is particularly suitable. The acid catalyst is preferably blended in the range of 0.01 to 10 parts by mass per 100 parts by mass (solid content) of cellulose nanocrystals. Furthermore, the cellulose nanocrystal-containing coating liquid may contain known additives, such as fillers, colorants, ultraviolet absorbers, antistatic agents, water-resistant agents, metal salts, colloidal silica, alumina sol, and titanium oxide, as necessary.
[0043] (Molded body) The molded article of the present invention is a molded article in which a layer containing the cellulose nanocrystals and polyvalent cationic resin contained in the cellulose nanocrystal-containing coating liquid of the present invention is formed on a substrate, and the cellulose nanocrystals are contained in a coating solution containing the cellulose nanocrystals in an amount of 1 m 2 When the oxygen permeability is 3.8 (cc / m2) at 23°C and 50% RH, 2 The molded article is capable of exhibiting excellent oxygen barrier properties, with a vapor barrier strength of less than 1000 psi (days atm), and when a layer containing cellulose nanocrystals and a polyvalent cation resin is formed on a substrate, the molded article can significantly improve the adhesion between the layer and the substrate layer. Furthermore, in the molded body of the present invention, the presence of the polyvalent cationic resin improves the interfacial peel strength with the layer made of a hydrophobic resin, so that the interfacial peel strength between the substrate, particularly the substrate made of a thermoplastic resin, and the layer containing cellulose nanocrystals and polyvalent cationic resin is 2.3 (N / 15 mm) or more, effectively preventing the occurrence of interlayer delamination.
[0044] In the molded article of the present invention, a layer having a mixed state capable of exhibiting excellent gas barrier properties and adhesion to a substrate can be formed by forming a layer made of the above-mentioned cellulose nanocrystal-containing coating liquid on a layer made of a polyvalent cationic resin. That is, although it is difficult to quantitatively express the mixed state of the layer formed by the coating liquid and polyvalent cationic resin of the present invention, it is formed only by mixing the polyvalent cationic resin and the cellulose nanocrystals in a state in which the self-organized structure of the above-mentioned cellulose nanocrystals is maintained. The inside of the layer formed by the coating liquid and polyvalent cationic resin of the present invention is characterized by the presence of cellulose nanocrystals and polyvalent cationic resin from near the outermost surface to the substrate.
[0045] [Polycationic resin] The polyvalent cationic resin used in the molded article of the present invention is a resin containing a water-soluble or water-dispersible polyvalent cationic functional group. Examples of such polyvalent cationic resins include water-soluble amine polymers such as polyethyleneimine, polyallylamine, polyamine polyamide epichlorohydrin, polyamine epichlorohydrin, polyacrylamide, poly(diallyldimethylammonium salt), dicyandiamide formalin, poly(meth)acrylate, cationic starch, cationic gum, gelatin, chitin, chitosan, etc., and among them, water-soluble amine polymers, particularly polyethyleneimine, can be preferably used.
[0046] [Base material] Examples of the substrate include, but are not limited to, a substrate made of a thermoplastic resin and a substrate made of paper. Examples of substrates made of thermoplastic resins include films, sheets, and molded articles in the form of bottles, cups, trays, pouches, etc., produced by using thermoplastic resins by means of extrusion molding, injection molding, blow molding, stretch blow molding, press molding, or the like. The thickness of the substrate made of a thermoplastic resin cannot be generally defined depending on the shape and application of the laminate, but in the case of a film, it is preferably in the range of 5 to 50 μm.
[0047] Examples of thermoplastic resins include olefin copolymers such as low-, medium- or high-density polyethylene, linear low-density polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-butene copolymer, ionomer, ethylene-vinyl acetate copolymer, and ethylene-vinyl alcohol copolymer; aromatic polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene terephthalate / isophthalate, and polyethylene naphthalate; aliphatic polyesters such as polylactic acid, polycaprolactone, and polybutylene succinate; polyamides such as nylon 6, nylon 6,6, nylon 6,10, and metaxylylene adipamide; polystyrene, styrene-butene copolymer, and polystyrene-butene copolymer. Examples of suitable resins include styrene-based copolymers such as butadiene block copolymers, styrene-acrylonitrile copolymers, and styrene-butadiene-acrylonitrile copolymers (ABS resins); vinyl chloride-based copolymers such as polyvinyl chloride and vinyl chloride-vinyl acetate copolymers; acrylic copolymers such as polymethyl methacrylate and methyl methacrylate-ethyl acrylate copolymers; polycarbonate, casein plastic, paramylon and other polysaccharide-based resins, starch-based resins, and cellulose-based resins; and regenerated celluloses such as acetyl cellulose, cellulose acetyl propionate, cellulose acetate butyrate, and cellophane, with polyethylene terephthalate being preferred. The thermoplastic resin may contain one or more additives such as pigments, antioxidants, antistatic agents, ultraviolet absorbers, lubricants, etc., as desired.
[0048] As the paper substrate, any paper can be used depending on the desired rigidity, etc. For example, known papers such as high-quality paper, imitation paper, art paper, coated paper, pure white roll paper, craft paper, label paper with improved water resistance, cup base paper, card paper, ivory paper, paperboard such as Manila cardboard, milk carton base paper, cup base paper, synthetic paper, clay-coated paper, water-resistant paper, and acid-resistant paper can be used. The thickness of the paper substrate is preferably in the range of 150 to 400 μm, and the basis weight of the paper substrate is preferably in the range of 150 to 350 g / m 2 It is preferable that the range is . Examples of paper substrates include shaped articles such as paper, sheet, cup, tray, carton, pouch, and box shapes produced by methods such as papermaking, coating, punching, slitting, laminating, joining, sealing, curling, and press molding.
[0049] In the laminate containing the molded article of the present invention, other layers may be formed as necessary in addition to the layer consisting of the substrate and the molded article. Although a layer made of a mixture of cellulose nanocrystals and a polyvalent cationic resin suppresses deterioration of gas barrier properties under high humidity conditions, it is desirable to further form a layer made of a conventional moisture-resistant resin such as an olefin resin, a polyester resin, or a cured reaction product of an epoxy resin and a polyamine resin.
[0050] (Method of Manufacturing Molded Product) The molded article of the present invention can be produced by a process of coating and drying a polyvalent cationic resin-containing solution on a substrate to form a layer composed of polyvalent cationic resin, and then coating and drying the cellulose nanocrystal-containing coating liquid of the present invention on the layer composed of polyvalent cationic resin, thereby producing a molded article having a layer composed of a mixture in which polyvalent cationic resin and cellulose nanocrystals are mixed in a specific mixed state.
[0051] [Coating and drying of polycation resin-containing solution] The polycation resin-containing solution preferably contains the polycation resin in an amount of 0.01 to 30 mass %, particularly 0.1 to 10 mass %, based on the solid content. If the amount of the polycation resin is less than the above range, the gas barrier property and the interfacial peel strength cannot be improved as compared with the case where the amount is within the above range, while if the amount of the polycation resin is more than the above range, the gas barrier property and the interfacial peel strength cannot be further improved, resulting in poor economic efficiency and possibly poor coatability and film-forming property. The solvent used for the polyvalent cation resin-containing solution may be water, alcohols such as methanol, ethanol, and isopropanol, ketones such as 2-butanone and acetone, aromatic solvents such as toluene, and mixed solvents of these with water. Furthermore, the polyvalent cation resin-containing solution may contain known additives, such as fillers, colorants, ultraviolet absorbers, antistatic agents, water-resistant agents, clay minerals, crosslinking agents, metal salts, colloidal silica, alumina sol, and titanium oxide, as necessary.
[0052] The amount of the polyvalent cationic resin-containing solution to be applied is determined based on the amount of cellulose nanocrystals (solid content) in the layer formed from the cellulose nanocrystal-containing coating solution, and the concentration of the polyvalent cationic resin-containing solution is used as a reference. 2 When the polyvalent cation resin is contained in an amount of 1.0 g per m 2 It is preferable to coat the polycation resin in an amount of 0.01 to 2.0 g per coating. If the amount of the polycation resin is less than the above range, the interfacial peel strength with respect to a hydrophobic substrate such as a polyester resin cannot be improved as compared with the case where the amount is within the above range, while if the amount of the polycation resin is more than the above range, the gas barrier property of the molded article may not be improved as compared with the case where the amount is within the above range. The coating method is not limited to the above, but can be, for example, spray coating, immersion, or coating with a bar coater, roll coater, gravure coater, etc. The coating is preferably dried at a temperature of 5 to 200° C. for 0.1 seconds to 24 hours. The drying process can be performed by oven drying, infrared heating, high-frequency heating, etc., but natural drying is also possible.
[0053] [Coating and drying of coating liquid containing cellulose nanocrystals] The cellulose nanocrystal-containing coating solution of the present invention described above has a cellulose nanocrystal (solid content) of 1 m 2 It is preferable to coat the coating amount so that the coating amount is 0.1 to 3.0 g per coating amount. The cellulose nanocrystal-containing coating solution can be applied and dried in the same manner as the polyvalent cation-containing solution, but drying is preferably performed at a temperature of 5 to 200° C. for 0.1 seconds to 24 hours. EXAMPLES
[0054] Examples of the present invention will be described below. Note that the following examples are merely examples of the present invention, and the present invention is not limited to these examples. The measurement methods for each item are as follows.
[0055] <Visible light transmittance> The visible light transmittance (%T) at 600 nm of a cellulose nanocrystal dispersion with a solid content of 2% by mass was determined using a spectrophotometer (UV-3100PC, Shimadzu Corporation).
[0056] <Particle size distribution> Using a laser diffraction particle size distribution analyzer (SALD-3100, Shimadzu Corporation), the average particle size, median diameter, and mode diameter were measured while diluting and dispersing cellulose nanocrystals in an aqueous dispersion with a solid content of 2% by mass. The light source of the device was a semiconductor laser with a wavelength of 690 nm. The measurement results with an absorbance of 0.015 or less and a refractive index of 1.55 were used for analysis.
[0057] <Oxygen permeability> Using an oxygen transmission rate measuring device (OX-TRAN2 / 22, manufactured by MOCON), the oxygen transmission rate (cc / m 2 ·day·atm) was measured.
[0058] <Example 1> <Preparation of Cellulose Nanocrystal-Containing Dispersion> Pulp was decomposed with 64% by mass sulfuric acid to prepare cellulose nanocrystals. The cellulose nanocrystals were concentrated and washed in an ultracentrifuge without being dried to prepare never-dried cellulose nanocrystals. Finally, the cellulose nanocrystals were added to ion-exchanged water so that the solid content was 2% by mass, and the cellulose nanocrystals were treated for 10 minutes in an ultrasonic disperser to prepare a cellulose nanocrystal-containing dispersion.
[0059] <Preparation of cellulose nanocrystal-containing coating solution> The cellulose nanocrystal-containing dispersion was diluted with ion exchange water so that the solid content of the cellulose nanocrystals was 1% by mass, and anhydrous citric acid, sulfuric acid, synthetic mica (hydrophilic swelling mica, manufactured by Katakura Co-op Agri Co., Ltd.), and polyvinyl alcohol (fully saponified type, manufactured by Kuraray Co., Ltd.) were added in 10 parts by mass, 2 parts by mass, 30 parts by mass, and 30 parts by mass per 100 parts by mass (solid content) of cellulose nanocrystals, and the mixture was stirred to prepare a cellulose nanocrystal-containing coating liquid with a pH of 3.
[0060] <Formed body having a layer containing a polyvalent cationic resin and cellulose nanocrystals> A molded article having a layer containing a polyvalent cationic resin and cellulose nanocrystals was produced by the following procedure. Polyethylenimine (PEI) (Epomin, P-1000, Nippon Shokubai Co., Ltd.) was applied to a corona-treated biaxially stretched PET film (Lumirror P60, 12 μm, Toray Industries, Inc.) substrate using a bar coater at a solid weight of 0.6 g / m 2 The coated film was dried at 50°C for 10 minutes in a hot air dryer (MSO-TP, manufactured by ADVANTEC) to solidify, and then coated with a bar coater so that the coating liquid containing 1% by mass of the cellulose nanocrystals produced by the above method was applied to the film so as to have a solid content of 1.0 g / m 2 The coating was then air-dried overnight at room temperature to prepare a molded article having a layer containing the polyvalent cationic resin and cellulose nanocrystals formed on the biaxially stretched PET film.
[0061] <Example 2> A cellulose nanocrystal-containing coating liquid was prepared by never-drying as in Example 1, and added to ion-exchanged water so that the final solid content of cellulose nanocrystals was 2% by mass. The liquid was then treated with an ultra-high pressure homogenizer for 10 minutes to prepare a cellulose nanocrystal-containing dispersion liquid. The cellulose nanocrystal-containing dispersion was treated in the same manner as in Example 1 to prepare a molded article having a cellulose nanocrystal-containing coating liquid and then a layer containing a polyvalent cationic resin and cellulose nanocrystals.
[0062] <Comparative Example 1> The pulp was decomposed with 64% by mass sulfuric acid, washed, and dried to prepare cellulose nanocrystals. 1 g (solid content) of the cellulose nanocrystals was added to ion-exchanged water and dispersed for 10 minutes using an ultrasonic disperser to prepare a cellulose nanocrystal-containing dispersion with a solid content of 2% by mass. The cellulose nanocrystal-containing dispersion was treated in the same manner as in Example 1 to prepare a molded article having a cellulose nanocrystal-containing coating liquid and then a layer containing a polyvalent cationic resin and cellulose nanocrystals.
[0063] [Table 1] [Industrial Applicability]
[0064] The cellulose nanocrystal-containing coating liquid of the present invention can form a dense crosslinked structure in which the cellulose nanocrystals are uniformly dispersed, and has excellent gas barrier properties even under high humidity conditions, so it can be used as a coating agent that can impart gas barrier performance.In addition, by forming a molded article having a layer made of a mixture of the cellulose nanocrystal-containing coating liquid of the present invention and a polyvalent cationic resin, it is possible to exhibit better gas barrier properties, and the interfacial peel strength with a hydrophobic substrate made of a thermoplastic resin or the like is also improved, so it is preferably used as a gas barrier laminate.
Claims
1. A coating liquid containing cellulose nanocrystals, comprising a cellulose nanocrystal dispersion, a water-soluble polymer, an inorganic layered compound and a polycarboxylic acid, characterized in that when the cellulose nanocrystal content of the cellulose nanocrystal dispersion is 1% by mass, the cellulose nanocrystals have an average particle size of 12.2 μm or less, a median diameter of 12.6 μm or less and a mode diameter of 17.0 μm or less as measured by a laser diffraction particle size distribution measuring device.
2. 2. The cellulose nanocrystal-containing coating liquid according to claim 1, wherein the water-soluble polymer is polyvinyl alcohol, and is contained in an amount of 0.1 to 50 parts by mass per 100 parts by mass of the cellulose nanocrystal (solid content).
3. 3. The cellulose nanocrystal-containing coating liquid according to claim 1 or 2, wherein the inorganic layered compound is mica, and is contained in an amount of 0.1 to 50 parts by mass per 100 parts by mass of the cellulose nanocrystal (solid content).
4. The cellulose nanocrystal-containing coating liquid according to any one of claims 1 to 3, wherein the polycarboxylic acid is citric acid and is contained in an amount of 0.1 to 50 parts by mass per 100 parts by mass of the cellulose nanocrystal (solid content).
5. The cellulose nanocrystal-containing coating liquid according to any one of claims 1 to 4, wherein the cellulose nanocrystal dispersion has a visible light transmittance of 2.1%T or more at 600 nm when dispersed in water with a solid content of 2% by mass of cellulose nanocrystals.
Citation Information
Patent Citations
High sulfate radical group grafted cellulose nanocrystal, preparation method and application thereof
CN108359017A
Cellulose nanocrystal-based waterborne acrylic coating
CN109593408A
Fine fibrous cellulose, method for producing the same, fine fibrous cellulose dispersion, and non-woven fabric
JP2013253200A
Cellulose nanofiber
JP2013256546A
Manufacturing method of coating liquid for forming gas barrier layer, gas barrier laminate and packaging material
JP2017071783A